Meningkatkan kualitas pembelajaran mahasiswa: Peran penting kemampuan mengatur waktu - Nabila, Sania (Maliki Interdisciplinary Journal, 2024)
In the world of education, especially among students, there are still many people who struggle to manage their time effectively and efficiently. This difficulty hinders their ability to improve the quality of their learning experience. The demanding nature of higher education often leaves individuals feeling overwhelmed and dissatisfied with their lifestyle. This sense of discomfort stems from the lack of time management skills demonstrated by students. The main focus of the educational process in schools is learning. The act of consciously changing attitudes and behaviors is a deliberate effort. To achieve behavior change, motivation is an important component in driving behavior. Motivating students to have a desire to learn is one of the factors that foster an encouraging environment. The drive to acquire knowledge and skills is essential for student motivation.Learning motivation can be divided into two typesStudents who have effective time management skills are better able to organize their learning compared to students who do not have such abilities.Individuals who lack the ability to control and determine the importance of the tasks performed are unable to manage their time effectively. In contrast, those with good time management skills have the ability to organize and schedule daily activities efficiently and effectively.Effective time management is essential for students to improve the quality of their learning experience. Many students struggle with time management, hindering their ability to improve their learning. The education system plays an important role in the development of individuals, and various entities emphasize the importance of education. Proper time management enables efficient organization and planning of daily activities, resulting in successful learning.